Introduction : mining the tar sands of big data - Driscoll, Michael E. (O'Reilly, 2011)
"Much of the world's most valuable information is trapped in digital sand, siloed in servers scattered around the globe. These vast expanses of data - streaming from our smart phones, DVRs, and GPS-enabled cars - can yield information to predict traffic jams, entertainment trends, even flu outbreaks. In this talk I'll discuss the promise of big data, which will come to pass in the coming decade, driven by advances in three principle areas: sensor networks, cloud computing, and machine learning."--Resource description page.